2009
DOI: 10.2131/jts.34.703
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional nascent polypeptide-associated complex (NAC) activity in ribosomes enhances adriamycin toxicity in budding yeast

Abstract: -To elucidate the role of ribosomes in the manifestation of adriamycin toxicity, ribos--otic model. This revealed that adriamycin toxicity was enhanced by loss of the Egd1 or Egd2 subunits of mitochondria or endoplasmic reticulum and in transcriptional activation in the nucleus. Because the loss of the Btt1 subunit had no effect on adriamycin sensitivity, the NAC conformation responsible for resistance to adriamycin appears to be the Egd1/Egd2 complex. We propose that functional NAC in the ribosome is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Screening of deletion collection strains for non-essential genes and studies with specific genes have revealed many genes and pathways in doxorubicin tolerance in yeast [ 14 , 15 ]. These include Ssl2 protein [ 16 ], Bsd2 protein [ 17 ], SUMO pathway [ 18 ], nascent polypeptide-associated complex activity in ribosomes [ 19 ], extracellular signal-regulated kinases ERK1 and ERK2 [ 13 ], endocytic Ark/Prk kinase [ 20 ], nitrogen permease regulator 2 ( Npr2 ) [ 21 ], cytochrome oxidase subunit IV gene [ 22 ], and overexpression of CLN1 , CLN2 and ERG13 [ 23 ]. Additionally, checkpoint and recombination functions in G1 and early S phase [ 14 ], as well as several proteins involved in DNA repair, RNA metabolism, chromatin remodeling, amino acid metabolism, and heat shock response [ 15 ], play roles in doxorubicin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of deletion collection strains for non-essential genes and studies with specific genes have revealed many genes and pathways in doxorubicin tolerance in yeast [ 14 , 15 ]. These include Ssl2 protein [ 16 ], Bsd2 protein [ 17 ], SUMO pathway [ 18 ], nascent polypeptide-associated complex activity in ribosomes [ 19 ], extracellular signal-regulated kinases ERK1 and ERK2 [ 13 ], endocytic Ark/Prk kinase [ 20 ], nitrogen permease regulator 2 ( Npr2 ) [ 21 ], cytochrome oxidase subunit IV gene [ 22 ], and overexpression of CLN1 , CLN2 and ERG13 [ 23 ]. Additionally, checkpoint and recombination functions in G1 and early S phase [ 14 ], as well as several proteins involved in DNA repair, RNA metabolism, chromatin remodeling, amino acid metabolism, and heat shock response [ 15 ], play roles in doxorubicin resistance.…”
Section: Introductionmentioning
confidence: 99%